Spiritual well-being and life satisfaction among older people residing in an urban community of Bhaktapur, Nepal - Pandey Bashyal, Sabita; Tuitui, Sangita (Journal of Karnali Academy of Health Sciences, 2025)
Background: Spirituality has been shown to predict well-being in old age. Spirituality and fulfillment of spiritual needs are considered priorities in the care of older people. Life satisfaction is influenced by several factors and is also an important issue in the care of older people. This study is intended to assess spiritual well-being and life satisfaction among older people residing in an urban community of Bhaktapur, Nepal. Methods: A cross-sectional study was conducted with 220 older residents of Bhaktapur Municipality from May to July 2022 using convenient sampling technique. Before data collection, all ethical and administrative approval and each respondent’s informed consent were obtained. Face to face interview was conducted using structured questionnaire of Spiritual Wellbeing Scale (score ranged from 20-120) and Satisfaction with Life Scale (score ranged from 5-35). SPSS V.20 was utilized to analyze the data using descriptive and inferential statistics. Results: The result showed that 61.8% had a moderate and 32.8% had high level of spiritual well-being with a mean score of 90.15 ± 17.78 (range 56–120). Majority, i.e. 62.3% of the older people were satisfied with their life with a mean score of 26.20 ± 6.21 (range 6 – 35). A significant moderate correlation (<p=0.001 and r=0.665) was found between spiritual well-being and life satisfaction. Conclusion: This study reinforces the view that spiritual well-being and life satisfaction have significant association. Therefore, family members and other caretakers may encourage the older people to participate in spiritual activities for their physical and psychological wellbeing